Thermomechanical stress in GaN‐LEDs soldered onto Cu substrates studied using finite element method and Raman spectroscopy. (27th July 2020) - Liu, E.; Conti, Fosca; Bhogaraju, Sri Krishna; Signorini, Raffaella; Pedron, Danilo; Wunderle, Bernhard; Elger, Gordon
Abstract: Local thermomechanical stress can cause failures in semiconductor packages during long‐time operation under harsh environmental conditions. This study helps to explain the packaging‐induced stress in blue GaN‐LEDs soldered onto copper substrates using AuSn alloy as lead‐free interconnect material. Based on the finite element method, a virtual prototype is developed to simulate the thermomechanical behavior and stress in the LED and in the complete LED/AuSn/Cu assembly considering plastic and viscoplastic strain. The investigations were performed by varying the temperature between −50°C and 180°C. To validate the model, the simulation results are compared to experimental data collected with Raman spectroscopy. Studies of the E 2 H phonon mode of GaN semiconductor are elaborated to understand the induced thermomechanical stress. The model enables evaluation of the stress in the interfaces of the assembly, which otherwise cannot be accessed by measurements. It serves to predict how assemblies would perform, before committing resources to build a physical prototype. Abstract : The reliability of high‐power semiconductors is strongly related to the assembly process. Mismatch of coefficient of thermal expansion and defects like large voids induces local thermomechanical stress, which causes early device failure. Studies of the E 2 H phonon mode of GaN semiconductor are elaborated to understand the induced thermomechanical stress and to validate finite element (FE) simulation models. A blue GaN‐LED soldered on copper substrate using AuSn alloy is investigated. Reliability of high‐power semiconductor chips is strongly related to assembly processes. Mismatch of thermal expansion coefficients of different materials and defects induces local thermomechanical stress, which causes early device failure. Studies of the wavenumber change of the E 2 H phonon mode of GaN are elaborated to understand the induced stresses and to validate a new developed FE simulation model. A blue GaN‐LED soldered onto a copper substrate using AuSn alloy is investigated.